Respuesta :
Answer:
y = ²/₃x + ⁴/₃
Step-by-step explanation:
The point-slope form of the equation of line: y - y₁ = m(x - x₁), where m is the slope and (x₁, y₁) is the point the line passing through.
y=m₁x+b₁ ║ y=m₂x+b₂ ⇔ m₁ = m₂
{Two lines are parallel if their slopes are equal}
y = 2/3x + 1 ⇒ m₁ = 2/3 ⇒ m₂ = 2/3
(-5, -2) ⇒ x₁ = -5, y₁ = -2
point-slope form:
y - (-2) = 2/3(x - (-5))
y + 2 = 2/3(x + 5)
y + 2 = 2/3x + 10/3 {subtact 2 from both sides}
y = 2/3x + 4/3 ← slope-intercept form
Answer:
y = ²/₃x + ⁴/₃
Step-by-step explanation:
The point-slope form of the equation of line: y - y₁ = m(x - x₁), where m is the slope and (x₁, y₁) is the point the line passing through.
y=m₁x+b₁ ║ y=m₂x+b₂ ⇔ m₁ = m₂
{Two lines are parallel if their slopes are equal}
y = 2/3x + 1 ⇒ m₁ = 2/3 ⇒ m₂ = 2/3
(-5, -2) ⇒ x₁ = -5, y₁ = -2
point-slope form:
y - (-2) = 2/3(x - (-5))
y + 2 = 2/3(x + 5)
y + 2 = 2/3x + 10/3 {subtact 2 from both sides}
y = 2/3x + 4/3 ← slope-intercept form